Association between Social Capital and Self-rated Health of Older People in Chandigarh, India - Rawal, Ishita; Kaur, Manmeet; Chakrapani, Venkatesan; Khanna, Poonam; Lakshmi, PVM; Kaur, Navkiran (Indian Journal of Community Health, 2017)
Background: Social capital reflect the degree of social cohesion in communities. Although studies have shown that social capital influences health, there is limited understanding about the role of social capital on physical and mental health of older people in India. Aims & Objectives: To assess the association between social capital and self-rated health among older people. Material &Methods: A cross-sectional study was conducted among 211 older people selected from 1563 households in urban and rural Chandigarh District. Standardized tools were used to measure social capital (Global Social Capital Survey) and self-rated health (SF-36). The association between social capital and physical and mental health dimensions of self-rated health was analyzed using multiple linear regression. Results: Participants’ mean age was 68.1 years (SD 7.6); about half were women. The mean total social capital score was 45.5 (SD 11.9). The mean physical and mental health dimensions of self-rated health scores were 1027.7 (SD 252.5) and 1416.9 (SD 487.7), respectively. Social capital was found to be a significant predictor of mental health dimension of self-rated health. Age and gender were found to be significant predictors of physical health dimension of self-rated health. Conclusion: Social capital influences mental health of older people. Interventions to improve social capital, in terms of strengthening relationships with family members and other social networks, can contribute to improving mental health of older people.